(3efgGL GdeSdes (3cJGH YbGFO hBOGH hCNdGb hYHGOGJ heYGedGJ (B/s - (3CHh HcQ GdLRGFQj, LGHQ Hf ehSi Hf YHO GdbGOQ,s 1921- ((3HjQhJ (B:s (3GdecJHI GdbjeI,s, 2005)
(3jJfGhd gPG GdcJGH GdYOjO ef GdehVhYGJ Yf GdYbjOI hGdBOGH hGdCNdGb hGdYHGOGJ hCUhd GdTQjYI GdESdGejI(B.s
Keywords: (3GdESdGes -- (3eJaQbGJs; (3GdCNdGb GdESdGejIs; (3GdYHGOGJ (B((3abg ESdGej(B)s; (3GdeYGedGJ (B((3abg ESdGej(B)s